Masyarakat Terhadap Perceraian Akibat Kekerasan Dalam Rumah Tangga (KDRT) Di Kecamatan Krejengan Kabupaten Probolinggo - karomah , Avita rohmatul (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Divorce is a breaking of the bond in a husband and wife relationship which means the breaking of the marriage law so that the two of them are no longer domiciled as husband and wife and no longer live together in a household. Divorce is not an agreement therefore, marital divorce may not be based on an agreement to divorce . Divorce is an emergency exit or alternative that can be chosen to resolve disputes in marriage. Divorce occurs because of various conflicts that cannot be resolved properly in the husband and wife's household. Therefore, before we go through a serious relationship, we think about it carefully first and also think with the family so that the household we live in will not result in divorce. In a household, disputes and quarrels between husband and wife are commonplace, but this is the beginning of divorce. Hope in forming a household mahligai after making a vow in front of the prince and promising to live together forever, and committing to create a household that is Sakinah Mawaddah and warahmah. maintain the integrity of their household and it turns out there is no other way except divorce. It can be said that divorce is the best way out and is the final decision for husband and wife in solving complicated problems.